Impact of Principal Leadership, Organizational Culture, and Teacher Welfare on Teacher Performance: A Case Study in Public Junior High Schools - Fony Apriliana Duka; Suyud Suyud (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research investigates how principal leadership, organizational culture, and teacher welfare impact teacher performance in public junior high schools located in South Sorong. Utilizing a quantitative methodology, data were gathered through surveys administered to teachers from multiple schools within the area. The study adopts an ex-post facto design. The target population comprised all 248 teachers employed at public junior high schools in South Sorong Regency. A total of 155 teachers were selected as the sample using a cluster random sampling method. The data were analyzed using a range of statistical techniques, including validity and reliability testing, normality checks, correlation analysis, regression analysis, and hypothesis testing. The findings reveal the following: (1) principal leadership has a positive and significant effect on teacher performance, contributing 11.6%; (2) organizational culture positively and significantly affects teacher performance by 15.6%; (3) teacher welfare has a positive and significant influence, accounting for 29.6%; and (4) the combined effect of principal leadership, organizational culture, and teacher welfare on teacher performance reaches 32.3%.